In the name of the euro: What have the EU's policies achieved in Greece? - Irene Kyriakopoulos (Intereconomics, 2014)
This paper reviews the novel policy measures developed by the EU to deal with insolvent member states and assesses their impact on Greece's political economy. Greece represents a major test case as a recipient of two bailout loans plus debt relief from private creditors. The paper examines the degree to which EU policies have been successful, evaluates the challenges that remain after four years of reforms and traces their implications for the future of European integration.
Keywords: 330; Haushaltsdefizit; Haushaltskonsolidierung; Schuldenübernahme; Wirtschaftliche Anpassung; EU-Politik; Europäische Integration; Wirkungsanalyse; Griechenland